Creative skills in solving environmental problems among kindergarten children - امل داود سلیم انوار فاضل عبد الوھاب الشوك (College of Education for Women, 2019)
Acquires this research importance of addressing the subject (environmental problems) with age group task, a category that children pre-school, and also reflected the importance of research, because the (environmental problems) constitute a major threat to the continuation of human life, particularly the children, so the environment is Bmchkladtha within kindergarten programs represent the basis of a hub of learning where the axis, where the kindergarten took into account included in the programs in order to help the development of environmental awareness among children and get them used to the sound practices and behaviors since childhood . The research also detected problem-solving skills creative with kids Riyadh, and because the relationship between the skills of creativity and problem-solving environmental starts always a sense of the problem and clear the roots of creativity in the awareness that there is a deficiency or obscure what needs to be solved, and thus became the style of solving the problem demand basis for learning as the child is facing in their daily lives much of the problems that require the use of methods to solve educated to confront them and the style of the creative solution to problems through the Provisions of creative skills (originality, flexibility, fluency and sensitivity to the problems). This prompted the researcher to do a field study, addressed the (environmental problems) on the children of Riyadh, this segment of society, certainly it feels too much suffering, but because of their young age, they can not deliver their voices to others, because most of the adults around them may not meet the needs and demands of helping get rid of them, this felt a researcher at the meet the needs of these children through the construction of a test based on the creative skills of the solution to environmental problems with this category .oahdf this search